To prove that the expressions \((x - 5)(x + 3)\) and \(2x^2 - x^2 - 2x - 20 + 5\) are equivalent, we'll expand Expression 1 and simplify Expression 2.
Expression 1: \((x - 5)(x + 3)\) Using the Distributive Property (FOIL method):
\[ (x - 5)(x + 3) = x\cdot x + x\cdot 3 - 5\cdot x - 5\cdot 3 \] \[ = x^2 + 3x - 5x - 15 \] \[ = x^2 - 2x - 15 \]
Expression 2: \(2x^2 - x^2 - 2x - 20 + 5\) Now, simplify Expression 2 by combining like terms:
\[ 2x^2 - x^2 = x^2 \] \[ -2x \] \[ -20 + 5 = -15 \] Thus, we have: \[ \text{Expression 2} = x^2 - 2x - 15 \]
Since both expressions simplify to \(x^2 - 2x - 15\), we conclude that they are equivalent.